Crystal Structure, Infrared Spectra, and Microwave Dielectric Properties of Ce2(Zr0.94Sn0.06)3(MoO4)9 Ceramics With Low Sintering Temperature - Tian, Huanrong; Liu, Xin; Yang, Yaokang; Wu, Haitao; Zhang, Zhiliang (Frontiers in Materials, 2020)
Ce2(Zr0.94Sn0.06)3(MoO4)9 (CZSM) ceramics were synthesized via a traditional solid-state method. The effects of Sn-substitution on phase composition, microstructure, and microwave dielectric properties as a function of sintering temperature were discussed. The XRD results indicated that all the samples exhibited a single phase. The chemical bonds of CZSM ceramics were calculated based on P-V-L theory, which could be used to evaluate the relationship between structure and microwave dielectric properties. The tendency of dielectric constant was depended on the theoretical dielectric polarizability and bond ionicity. Moreover, the improvement of Q·f value was ascribed to the increase of packing fraction. The reduced τf value could be explained by decrease of the bond energy, enhanced the co-efficient of thermal expansion and increase of bond valence (VZr(Sn)). The complex permittivity values were obtained from infrared reflectivity spectra. The dielectric permittivity and loss were 10.92 and 3.08 × 10−4, respectively, which agreed well with the measured value. Typically, the optimal microwave dielectric properties of εr = 10.35, Q·f = 59,660 GHz (at 9.70 GHz), and τf = −7.52 ppm/°C were achieved in CZSM ceramics sintered at 800°C for 6 h.